Assessing Mammals Distribution and their Relative Abundance in Kailash Sacred Landscape, India - Hussain, Ajaz; Sathyakumar, S.; Rawat, G.S.; Adhikari, B.S. (Indian Forester, 2024)
Present paper deals with the distribution and relative abundance of mammals in the Indian part of Kailash Sacred Landscape (KSL), using presence data obtained from different field methods and camera traps for the study period of four years between October 2014 and January 2017. The KSL India is among the neglected landscape in the context of faunal assessment and their monitoring in the Indian Himalaya. The present study provides the relative abundance and suitable area map. This study was conducted in four forest ranges of KSL India. Together all methods resulted in 30 species of mammals with 8 species that have global conservation significance and a new record of tiger (Panthera tigris) distribution in Askot Wildlife Sanctuary. Other key species detected are snow leopard (Panthera uncia), Asiatic black bear (Ursus thibetanus), common leopard (Panthers pardus) and musk deer (Moschus chrysogaster). Among carnivores, the common leopard (1.64±0.04) and palm civet (0.75±0.04) were found to have the most abundant while wild pig (31.00±0.04) and barking deer (16.21±0.01) were the most abundant prey species. Using presence-only data from camera traps and trail walk and different environmental variables authors assessed the suitable area for various mammalian species namely, common leopard, Asiatic black bear, leopard cat, Himalayan goral, barking deer, wild pig, sambar, and rhesus macaque. To create suitable area maps, they selected 11 environmental variables. The distribution model based on the presence location was relatively successful and showed a high level of accuracy during model validation with the present locations. The final suitability area map of the species can be used to conserve, manage and monitor the mammalian species and their habitat in KSL India.